Hidden Reactivity of Barbituric and Meldrum’s Acids: Atom-Efficient Free-Radical C–O Coupling with N-Hydroxy Compounds - Krylov, Igor B.; Paveliev, Stanislav A.; Budnikov, Alexander S.; Segida, Oleg O.; Merkulova, Valentina M.; Vil’, Vera A.; Nikishin, Gennady I.; Terent’ev, Alexander O. (Synthesis, 2021)
The reactivity of CH-acidic and structurally related enol-containing heterocycles towards N-oxyl radicals is disclosed. Traditionally, these substrates have been considered as reactants for ionic transformations. Highly selective and efficient N-oxyl radical mediated C–O coupling of substituted barbituric or Meldrum’s acids with N-hydroxy compounds (N-hydroxyimides, hydroxamic acids, oximes, and N-hydroxybenzotriazole) was achieved using inexpensive manganese-containing salts as oxidants. Metal-free C–O coupling was demonstrated using diacetyliminoxyl as both the oxidant (hydrogen-atom acceptor) and the coupling partner.
Keywords: radicals; oxidative coupling; NHPI; barbituric acids; Meldrum’s acids